LARANGAN MEMBUNUH DAN SOAL KEPUTUSAN HUKUMAN MATI HAKIM (Analisis Kasus Vonis Mati Ferdy Sambo Berdasarkan Teori Fontes Moralitatis, Kitab Suci dan Ajaran Gereja): Indonesia - Andreas Mariano (Aggiornamento, 2023)
This article discusses the prohibition of killing with an analysis of Ferdy Sambo's death sentence. Lately there has been a lot of public discussion about this death sentence. This reveals as if society strongly supports the death penalty. In this analysis, moral theology seeks to find out the good and the bad if the sentence is carried out. This is also a dilemma because in fact, the Catholic Church does not support the death penalty. Such a model of punishment is very contrary to the main Christian teachings, namely, love. Apart from that, it is hoped that each individual will understand the meaning of life. This cannot be denied because basically, humans are God's creation so only He has the right to take back human life. In this paper, the method used is literature study which focuses on understanding the meaning of death penalty and murder in the light of the Bible and moral theology. These two things cannot be separated by remembering that in them there are many lessons about life. Therefore, avoiding killing is salvation for all human beings. Keywords: Human Rights, Death, Theology